Evaluation of macular and optic nerve head changes by optical coherence tomography angiography in glaucomatous eyes - Ezzeldin G Mohamed; Tamer H. Elsersy; Ayman M Lotfy; Ahmed M Elshabrawy (Journal of the Egyptian Ophthalmological Society)
Background Optical coherence tomography angiography (OCTA) is introduced as a safe, noninvasive, and dye-free technology that provides an assessment of both large vessels and microvasculature of the retina and some parts of the choriocapillaris. Measuring vessel densities using OCTA at both the macula and optic nerve head (ONH) in glaucomatous eyes and comparing them with those of normal eyes will give us an idea about the effect of glaucoma on vessel densities and the role of OCTA in controlling and monitoring glaucoma progression, which remains despite the various medical and surgical treatment options, the second most common reason of blindness worldwide.